A Comparative Study on the Effectiveness of Flat and Spin Serves in Direct Points Simulation Matches - Ians Aprilo; Poppy Elisano Arfanda; M. Adam Mappaompo; Anung Priambodo; Muhammad Sulfa (Universitas Negeri Semarang, 2025)
This study aims to compare the effectiveness of two service techniques, namely flat serve and spin serve, on direct point acquisition in a simulated tennis match situation. The subjects of the study consisted of 20 male junior tennis players, aged 14–16 years, who were divided into two groups based on service technique. Each group was to use one type of serve consistently during three sets of simulated matches. The variables observed included the number of direct points, service speed, accuracy, rally length, and number of double faults. The results of the independent t-test analysis showed that the flat serve group scored a higher average direct points mean, 9.2; SD = 2.15, than the spin serve group mean, 6.8; SD 1.69, with a t-value = 2.74; p = 0.013. Supporting analysis also showed that the flat serve had higher speed, while the spin serve was superior in accuracy and rally duration. These findings indicate that the flat serve is more effective for a fast point scoring strategy, while the spin serve is more suitable for long rallies and game control. Therefore, coaches are advised to integrate service variation training as part of the development of athletes’ playing strategies.